The Trend of Technology Pedagogical Content Knowledge (TPACK) Research in 2012-2022: Contribution to Science Learning of 21st Century - Bahtiar Bahtiar; Yusuf Yusuf; Aris Doyan; Ibrahim Ibrahim (Postgraduate, University of Mataram, 2023)
The use of TPACK in 21st Century Science learning can facilitate teachers and students to be more active in learning and make it easier for students to have the expected 21st-century competencies. This study aims to identify and analyze TPACK research trends in 21st-century science learning in the form of TPACK documents, classification of journal rankings, classification of authors and their country of origin, and classification of keywords. This research is qualitative research. The data used in this study were obtained from documents indexed by Google Scholar from 2012-2022 using Publish or Perish and dimension.ai. Research procedures using PRISMA guidelines. Methods of data analysis using bibliometric analysis assisted by VOSviewer software. The results of the analysis show that the trend of writing TPACK articles in 21st Century Science learning has increased significantly from 2016 to 2020. Most journals that contain articles about TPACK in 21st Century Science learning are Educational and Information Technologies and Computers & Education. The results of the density mapping analysis show that the themes that are rarely researched are ICT investigation, curriculum, effectiveness, teacher knowledge, foreign language, teacher education, and TPACK instrument.